Renewing the Covenant: Insights for Right and Just Living from the Book of Hosea - Alexander George Nicolaides; Angelo Nicolaides (Pharos Journal of Theology)
The book of the prophet Hosea (meaning: 'he saves') was written in the 8thCentury CE towards the end of the northern Kingdom at a time when Judah and Israel we're still relatively intact. The prophet Amos warned the people of Yahweh that they needed to accept the judgement of God who is just and realise that the Assyrians would most likely annihilate them. Hosea entered the picture and most of his utterances revolved around the fact that Israel was unfaithful, and this is the hallmark of his writing. The book of Hosea casts a gaudy light upon the ethical condition of Ephraim (Israel during its final years at a time when they adopted the debased practices of their Canaanite neighbours. Hosea found himself in a position to proclaim the truth of what would happen to the people who had lost their faith in themselves and also in Yahweh, but this was not necessarily Yahweh’s final word. Hosea displayed great insight concerning the truth of God's mercy which was critical then as it is today. Hosea (5:6) warns "They will go with their flocks and herds to seek Yahweh, but they will not find Him; He has withdrawn from them". Later in Hosea (5:15) Yahweh warns "I will go away and return to My place until they acknowledge their guilt and seek My face; in their affliction they will earnestly seek Me". God requires repentance from people and atonement with Him as Lord of all. This article pursues the issue of God’s apostasy or "withdrawing" from His people. We may seek the Lord and not find Him because our attitude may be wrong, and how we seek Him is not acceptable – we are called to seek Him with a sincere and contrite heart and with all our soul (Deuteronomy 4:29). What is the theological exegesis of the selected verse and what were and are the dogmatic realities expressed in it. In addition, what can we in our current troubled world learn from the passage and what causes God to withdraw from us? What can Hosea teach the legal profession today? Though we may be dark as can be in spirit, and living in the shadows, God is by contrast an ever intensely radiant light holding out for the restoration of His people if they repent and place their faith and trust in Him.